Outstanding Patient Service with Web-Based Information System - Agung Suryadi; Syahril Anuar Idris; Rika Wulandari (Global Health Science Group, 2022)
Information technology in the health sector is very important, one of which is in health clinics that can support data and information services that are more efficient, accurate and safe. Clinics are providers of basic and specialist medical services in the treatment of early-stage diseases. Based on previous research surveys, an outpatient clinic information system has been built using the Microsoft Visual Studio 2008 programming language which has the disadvantage of only supporting the Windows operating system and is vulnerable to viruses and there is no diagnostic coding feature on the system. Efforts to overcome these shortcomings are by building a Web-Based Outpatient Clinic Information System. The type of research used is descriptive research with observation data collection methods and literature study using a cross-sectional approach, and secondary data sources. The research variables consisted of outpatient procedure flow, patient data, doctor data, polyclinic data, examination data, action data, diagnostic data, drug data, registration data, officer data, and outpatient information systems. The system development method used is the System Development Life Cycle (SDLC). The Web-Based Outpatient Clinic Information System is obtained from the patient data input process, doctor data input, polyclinic data input, action data input, diagnosis data input, drug data input, examination data input, registration data input, officer data input then processed by the registration process and the examination process to produce output in the form of patient data reports, doctor data reports, polyclinic data reports, officer data reports, diagnostic data reports, action data reports, drug data reports, registration data reports and examination data reports. The system is built using the PHP programming language with a MySQL database. The application of a web-based outpatient information system can simplify and speed up data processing and services to patients and the system is easy to develop.